POTENSI MINYAK JARAK PAGAR (Jatropha Curcas L) SEBAGAI BAHAN AKTIF LOTION ANTINYAMUK ANOPHELES SP - Siti Juariah (Akademi Kesehatan John Paul II Pekanbaru, 2022)
Malaria is an infectious disease caused by parasites (protozoa) derived from the genus plasmodium which is transmitted through the bite of the Anopheles mosquito. Malaria is transmitted through sufferers to healthy people by the Anopheles mosquito. Transmission of malaria between humans is carried out by female mosquitoes of the genus Anopheles. One of the prevention of the spread of malaria is by controlling the larvae of the Anopheles mosquito, the control can be done by using Repellent . The purpose of this study is to find out the potential of distance fencing essential oil lotion (Jatropha Curcas L) can be as a natural insecticide repellent (repellent) against mosquitoes Anopheles. This research was conducted using exprimental laboratory method with research design focus to know the effect of antinyamuk lotion antinyamuk oil distance fencing (Jatropha Curcas L) as repellent against mosquitoes Anopheles. Based on research obtained on the concentration of 20% of mosquitoes that stay away as much as 7 heads (70%) for 5 minutes, the concentration of 25% of mosquitoes that stay away as much as 8 heads (80%) for 5 minutes, and at a concentration of 30% of mosquitoes that stay away as much as 10 heads (100%) for 5 minutes. While the control (+) within 5 minutes mosquitoes away as many as 10 heads (100%) and control (-) no mosquitoes to stay away as much as 10 heads (0%). The results of this study can be concluded that the essential oil lotion distance fence (Jatropha Curcas L) the most effective as repellent at a concentration of 30% this extract is capable as a repellent and serves as a natural insecticide against mosquitoes Anopheles